Systems thinking for general surveillance programs – using leverage points to guide program management - Ticehurst, Jenifer L.; Kruger, Heleen (Frontiers in Ecology and Evolution, 2023)
With the increasing threat of pests, weeds and diseases to agriculture, the environment and our way of life, governments are becoming more reliant on general surveillance to fill biosecurity surveillance gaps. That is, engaging people from all walks of life in the monitoring and reporting of pests, weeds and diseases. It is often thought that instigating a general surveillance program simply requires the development of reporting tools and creating awareness of the program among intended target groups, but this is a simplistic view. This paper explores whether a broader approach identifies better ways to implement general surveillance programs to meet their goals and remain sustainable over the long-term, and therefore assist in program management. A systems thinking approach was used to identify the components within general surveillance programs, and their interactions. These components are the actors or people involved and their relationships; infrastructure like reporting tools and resources; formal and informal rules; and species or diseases of interest and their environment (included to account for the biophysical context). We explored what helped and hindered the design and implementation of general surveillance programs, drawing on international literature and the experiences of people in nine case studies from across Australia and New Zealand. Systems thinking helped to identify leverage points in the case studies, including feedback loops and information flow paths, and facilitated thought on how they can be used to improve programs. For example, sharing knowledge and experiences of actors from throughout the program being notifiers (i.e. the people who report pests, weeds and diseases), laboratory or herbarium staff, funding bodies, policy makers and others, built trust and ownership in the program and facilitated learning and self-organisation. This increased the capacity for innovation, adaptation, and continual improvement, leading to ongoing program benefits. Approaching program management using systems thinking helps structure program monitoring and evaluation and better target effort and resources to improve performance. However, this requires a dedicated program coordinator (or coordination team) with adequate resources to identify challenges and opportunities and adapt the program accordingly.